Mil as a Main Component of Lifelong Learning in Mediatized Society (A Model for Uzbekistan) (Eurasian Journal of Media and Communications, 2022)
This article focuses on the development of MIL and MIL education in Uzbekistan, one of the developing countries in Central Asia. As a practical study, observations were made on the results of MIL training conducted with schoolchildren based on foreign aid projects. On this basis, proposals and recommendations on the current situation and ways to develop MIL, reflecting the level of MIL of the population at different ages, will be put forward. The sphere of MIL began to gain popularity Uzbekistan with projects of foreign organizations. So far, trainings for journalists, school and higher education teachers, and journalists have been organized, and the necessary textbooks, manuals have been published. In general, the country has the necessary conditions for the organization of education in the field of MIL. Now, their implementation and implementation of MIL education at all levels of the education system will help the population to increase the level of MIL and find their place in the current mediated world, in the modern labour market, and in social life. On this basis, the article MIL was shown as a main component of lifelong learning